2012
DOI: 10.1165/rcmb.2011-0385oc
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Overexpression of Receptors for Advanced Glycation End-Products by Alveolar Epithelium Induces an Imbalance between Proliferation and Apoptosis

Abstract: Receptors for advanced glycation end-products (RAGEs) are multiligand cell surface receptors highly expressed in the lung that contribute to alveolar epithelial cell differentiation during embryogenesis and the modulation of pulmonary inflammation during disease. When RAGEs are overexpressed throughout embryogenesis, severe lung hypoplasia ensues, culminating in perinatal lethality. However, the possible mechanisms that lead to the disappearance of pulmonary tissue remain unclear. A time course of lung organog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 61 publications
2
33
0
1
Order By: Relevance
“…Such pathways include those associated with fibroblast growth factors (Fgfs), sonic hedgehog (Shh), bone morphogenetic protein 4 (Bmp4), vascular endothelial growth factors (Vegfs), thyroid transcription factor 1 (TTF-1), and Wnts (Burri, 1984;Cardoso, 2001;Copland and Post, 2004;deMello et al, 1997;Gluck, 1978;Stogsdill et al, 2012;Ten Have-Opbroek, 1991;Torday, 1992). When these or other important genetic pathways are defective or delayed, pulmonary hypoplasia or pulmonary agenesis may occur resulting in abnormally low or absent bronchopulmonary segments and terminal alveoli (Ballard, 1980;Stogsdill et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such pathways include those associated with fibroblast growth factors (Fgfs), sonic hedgehog (Shh), bone morphogenetic protein 4 (Bmp4), vascular endothelial growth factors (Vegfs), thyroid transcription factor 1 (TTF-1), and Wnts (Burri, 1984;Cardoso, 2001;Copland and Post, 2004;deMello et al, 1997;Gluck, 1978;Stogsdill et al, 2012;Ten Have-Opbroek, 1991;Torday, 1992). When these or other important genetic pathways are defective or delayed, pulmonary hypoplasia or pulmonary agenesis may occur resulting in abnormally low or absent bronchopulmonary segments and terminal alveoli (Ballard, 1980;Stogsdill et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin and eosin (H&E) staining was performed to observe general lung morphology. To perform immunostaining for specific markers and immunoflorescence, slide samples were dehydrated, deparaffinized, processed with antigen retrieval by citrate buffer, and incubated with primary and secondary antisera that utilize HRP conjugation with Vectors Elite Kit (Vector Laboratories; Burlingame, CA) (Reynolds et al, 2003;Reynolds et al, 2011;Stogsdill et al, 2012). Antibodies that were used include: Anti-Cldn6 goat polyclonal antibody (C-20, 1:100; Santa Cruz Biotechnologies, Santa Cruz, CA), proliferating cell nuclear antigen (PCNA, SC-7907, 1:500; Santa Cruz Biotechnology), thyroid transcription factor 1 (TTF-1, WRAB-1231, 1:100; Seven Hills BioReagents, Cincinnati, OH), forkhead box A2 (FoxA2, WRAB-1200, 1:100; Seven Hills BioReagents), Clara cell secretory protein (CCSP, WRAB-3950, 1:100; Seven Hills BioReagents), and Surfactant Protein-C (SP-C, WRAB-76694, 1:100; Seven Hills BioReagents).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…Furthermore, the optimal regulation of RAGE expression is a prerequisite for normal lung development. Mice overexpressing RAGE during lung embryogenesis show altered respiratory epithelial cell differentiation, severe lung hypoplasia and exhibit 100% perinatal mortality rates [64]. These observations suggest that tight regulation of RAGE expression is a requirement for alveolar epithelial cell differentiation.…”
Section: The Role Of Rage In Lung Physiologymentioning
confidence: 96%
“…Normal ATI cell differentiation and phenotype [22,50,51] Normal: embryonic stages [50,51] Tumorigenesis: cancer cell regression to embryonic phenotypes [37,[52][53][54][55][56][57][58] Normal ATI cell adhesion, spreading and stability [22] Decreased adhesiveness, increased migration, enhanced invasiveness [15,22,37,59-61] Normal alveolar cell apoptosis Evasion of apoptosis [15,16,29,59, 60] Normal alveolar function -gas exchange [22,62] Malignant behavior [59,60,61,63] Normal lung architecture [22,64] Malignant tissue and tumor stroma reorganization and modification [15,16,29,59-61] Normal cell-to-cell and cell-to-matrix communication Disruption of normal communication -cell isolation and autonomy explain the difference in binding affinity between different ligands, since each one of them possesses its own specific electrostatic signal. Touré et al showed that neutrophils exhibit enhanced adhesiveness and decreased migration on AGE-modified collagen in comparison to non-modified collagen [68].…”
Section: Normal Rage Expression Suppressed Rage Expressionmentioning
confidence: 99%
“…Эктодомен RAGE состоит из трех молекул Ig с V-, C1-и C2-доменами, которые отвечают за взаимодействие со специфичными лигандами [4]. RAGE опосредует многие физиологические функции, такие как рост нейронов, выживание и регенерация, игра-ет важную роль в воспалительных реакциях, индуцируя продукцию провоспалительных цитокинов и хемокинов, способствует элиминации апоптотических клеток, явля-ется главным медиатором врожденного иммунного ответа [1,5]. RAGE может участвовать и в ряде патологических процессов, включая сахарный диабет, болезнь Альцгей-мера, системный амилоидоз и опухолевый рост [6].…”
Section: Rage-белки: общие представления о регуляторной активностиunclassified